2017
DOI: 10.1186/s12888-017-1196-3
|View full text |Cite
|
Sign up to set email alerts
|

The content of delusions in a sample of South African Xhosa people with schizophrenia

Abstract: BackgroundAlthough the relationship between cultural beliefs and schizophrenia has received some attention, relatively little work has emerged from African contexts. In this study we draw from a sample of South African Xhosa people with schizophrenia, exploring their cultural beliefs and explanations of illness. The purpose of the article is to examine the relationship between this cultural context and the content of delusions.MethodsA sample comprising 200 Xhosa people with schizophrenia participating in a So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…For some individuals, different threats may be more salient or more likely and this might well be reflected in the content of delusions across individuals (e.g. see (96)). Secondly, we suggest additional focus is needed on how people perceive social groups, including processes relating to identification with in-group and categorising others as out-group, and how these processes may be altered in people experiencing severe paranoia.…”
Section: Discussionmentioning
confidence: 99%
“…For some individuals, different threats may be more salient or more likely and this might well be reflected in the content of delusions across individuals (e.g. see (96)). Secondly, we suggest additional focus is needed on how people perceive social groups, including processes relating to identification with in-group and categorising others as out-group, and how these processes may be altered in people experiencing severe paranoia.…”
Section: Discussionmentioning
confidence: 99%
“…People used to use witchcraft by practising exoteric rites with the assistance of hallucinogenic substances, “which are themselves basically forces of destruction” [ 73 – 74 ][ 75 76 ]. Campbell [ 77 ] found that some Xhosa patients in South Africa who were diagnosed with schizophrenia attributed their mental illness to witchcraft and stated that they were possessed by an internal force, displaying a passive attitude and describing hallucinations [ 78 ][ 79 – 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The H3Africa SAX study, which aims to identify genes responsible for schizophrenia, has not yet reported on genetic findings. However, the study has contributed a number of papers on schizophrenia symptomatology, 13 community engagement, 14 and ethical issues. For example, given previous work on the relationship between schizophrenia and cultural beliefs, we undertook a study of the content of delusions in a subsample of participants.…”
Section: Preliminary Discoveries From Genomic Research In H3africamentioning
confidence: 99%
“…This explanation aligns well with the understanding of jealousy-induced witchcraft in southern African communities, and highlights the important role that culture plays in the content of delusions. 13 …”
Section: Preliminary Discoveries From Genomic Research In H3africamentioning
confidence: 99%